Concurrent self-use of Herbal and Synthetic Medicines in Kurdistan Region-Iraq. - Adham, Aveen N.; Mohammed N. Sabir; Abdulqader, Dilbreen H.; Naqishbandi, Alaadin M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
In many parts of the world, there are rich traditions for the use of herbs in treatment of many disorders. This study is compared self-use of concurrent medicines (herbal and synthetic) (CM) with herbal only medicines (HM) among people of different genders, ages, and education levels in Kurdistan Region major cities (Erbil, Suleimaniyah, and Duhok). Self-administered structured questionnaires were randomly distributed among 587 respondents. The information obtained comprises the demography, gender, age, education level, previous self-use of CM or HM and indications for which HM were used.The highest ratio of respondents were males (50.6 %), herbal and concurrent medicines users were (15.8%) and (84.2 %) respectively. In all age groups, ratio of concurrent medicines users were higher than herbal medicines (p< 0.05), age groups of 31-40 and 51-60 years showed higher ratio among respondents with (23.5%) and (94.3%) for herbal and concurrent medicines, respectively. Among users of different educational levels, ratio of concurrent medicines were higher than herbal medicines (p< 0.01), university graduate and primary school educational levels were with higher ratio of (33.9%) and (93.9%) for herbal and concurrent medicines, respectively. The highest percentage of herb users was among people who suffered from gastrointestinal problems (59%), respiratory tract (39%) and cardiovascular system problems (36%), while musculoskeletal conditions were less often treated with herbs in Kurdistan Region (9%). Almost 104 plant species were mentioned during the interviews with respondents belonging to 57 families, the most diverse one Umbelliferae, followed by Brassicaceae, Asteraceae and Rosaceae.
Keywords: Herbal medicinesConcurrent medicinesKurdistan Region